2022
DOI: 10.3390/agronomy12112674
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Water-Fertilizer-Air-Coupling Drip Irrigation on Soil Health Status: Soil Aeration, Enzyme Activities and Microbial Biomass

Abstract: In order to investigate the effects of water-fertilizer-air-coupling drip irrigation on soil health status, including soil aeration (SA), enzyme activity (EA) and microbial biomass (MB), and its response relationship, this glasshouse experiment was conducted using tomato as the test crop, and we designed two fertilization gradients of 135 and 180 kg N·ha−1, two irrigation levels of 0.6-fold and 1.0-fold of the crop-pan coefficient, and two aeration treatments of 5 and 15 mg·L−1 for the three-factor and two-lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…Second, the nano-bubble irrigation systems should be responsive to soil aeration conditions. Soil aeration must be improved for enhancing soil eco-physical conditions and increasing crop yield and productivity [58]. Considering the variations in crop growth conditions across different natural environments, nano-bubble irrigation technology must be continuously refined and tested.…”
Section: The Applicability Of Nano-bubble Irrigation Can Be Strengthe...mentioning
confidence: 99%
“…Second, the nano-bubble irrigation systems should be responsive to soil aeration conditions. Soil aeration must be improved for enhancing soil eco-physical conditions and increasing crop yield and productivity [58]. Considering the variations in crop growth conditions across different natural environments, nano-bubble irrigation technology must be continuously refined and tested.…”
Section: The Applicability Of Nano-bubble Irrigation Can Be Strengthe...mentioning
confidence: 99%
“…By providing water and nutrients directly to the root zone, DRIP promotes nutrient uptake, plant growth, and improved nutritional value [43,44]. Moreover, DRIP reduces soil compaction, enhances root respiration, and increases soil enzyme activities and fertility, resulting in increased availability and uptake of nutrients and leading to higher feed value of forage [41,45]. Additionally, DRIP minimizes weed growth and competition, enabling forage plants to receive more nutrients and sunlight and leading to higher-quality forage [46,47].…”
Section: Forage Qualitymentioning
confidence: 99%
“…Previous studies have found a strong positive effect of moisture on soil enzyme activity, with higher moisture content leading to better binding of soil enzymes to substrates, which in turn promotes root development and overall plant growth [16]. It could also influence environmental factors such as soil temperature and moisture, which could affect crop uptake and utilization [17]. Seo et al [18] concluded that elevated temperatures enhance phenol oxidase activity and increase the reaction rate of phenol oxidase to promote soil carbon cycling.…”
Section: Introductionmentioning
confidence: 99%